Trajectories of Leisure-Time Physical Activity and Their Associations With Subjective Cognitive Decline (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study investigates trajectories of leisure-time physical activity (LTPA) among ageing people and how these trajectories are associated with subjective cognitive decline. Furthermore, the study seeks to explore whether these trajectories vary by occupational class.Methods: We utilised survey data from the Helsinki Health Study, a longitudinal cohort (n = 8,960, 80% women) of employees of the City of Helsinki (2000–2022). LTPA was quantified as weekly metabolic equivalent hours (MET-h). LTPA change (2000–2022) was categorised as repeated high (63%), increasing (low -> high) (13%), decreasing (high -> low) (14%), and repeated low (10%). The cut-off for low (